The Contributions Of Alonto To The Development Of Islamic Thought In The Philippines (1914-2002) - Mohammad Nashief S. Disomimba; Kalsombnti Ali (American Research Institute for Policy Development, 2024)
This paper examines the contributions of Alonto to the development of Islamic thought in the Philippines, and it will clarify his Parliamentary struggle, his establishment of Islamic University of the Philippines, his views on Islamic education and also the main characteristics of his Islamic thought in the Philippine Islands.The tendency of giving priority to discuss the some major contributions of Alonto to the development of Islamic thought in the Philippines is to clarify and trace the hidden and explore the reality of Islamic thought in the Philippine Islands. To address this limitation, an analytical study is conceived to foreground of his some major contributions to the development of Islamic thought in the Philippines. The objectives of this study is to identify and trace the development of Islamic thought, to understand its reality, to summarize the views of Alonto’s Islamic thought, and to forward analytical framework of the reality of the development of Islamic thought in the Philippine Islands. Discourse Analysis will use in this study in order to identify the elements of the Alonto’s islamic thought, contextualizing and examining the factors that shaped Alonto’s Islamic thought, synthesizing and understanding/confirming/clarifying the reality of his contribution to development of Islamic thought from the others, summarizing the views of the others, quoting/citing the statements of Muslim Scholars. The study singles out first that the Alonto’s Islamic thought no dichotomy to disconnect its teachings and understanding to each other and no contradictory between the Filipino Muslim Scholars about his Islamic thoughts. Alonto raised the level of his involvement by collaborating with international Islamic universities, institutions, and centers. His approach to spread and development of Islamic thought is primary a combination of his western educational background grounded based on the the Holy Qurān, and the teachings of Prophet Mohammad peace be upon him. At the end, the study focused on Alonto’s contributions to the development of Islamic thought and gives a critical analysis